2019
DOI: 10.1021/acs.jmedchem.9b01287
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Agonist of the Type 1 Lysophosphatidic Acid Receptor (LPA1), UCM-05194, Shows Efficacy in Neuropathic Pain Amelioration

Abstract: Neuropathic pain (NP) is a complex chronic pain state with a prevalence of almost 10% in the general population. Pharmacological options for NP are limited and weakly effective, so there is a need to develop more efficacious NP attenuating drugs. Activation of the type 1 lysophosphatidic acid (LPA 1 ) receptor is a crucial factor in the initiation of NP. Hence, it is conceivable that a functional antagonism strategy could lead to NP mitigation. Here we describe a new series of LPA 1 agonists among which deriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…Therefore, these neurons express a specialized setup of receptors and channels that can be activated by mechanical, thermal, or chemical stimuli and contribute to typical symptoms of CIPN as hyperalgesia, allodynia, or numbness ([ 13 , 14 , 15 ]. Several of these receptors or channels such as voltage-gated calcium channels or type 1 lysophosphatidic acid (LPA 1 ) receptors are discussed as playing a critical role in the induction of polyneuropathies or neuropathic pain in different models ([ 16 , 17 , 18 , 19 , 20 ]. Several cation channels facilitate nociception, e.g., the transient receptor potential channels (TRP), a family of cation channels that are crucial transducers of nociceptive stimuli contributing to sensory input.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these neurons express a specialized setup of receptors and channels that can be activated by mechanical, thermal, or chemical stimuli and contribute to typical symptoms of CIPN as hyperalgesia, allodynia, or numbness ([ 13 , 14 , 15 ]. Several of these receptors or channels such as voltage-gated calcium channels or type 1 lysophosphatidic acid (LPA 1 ) receptors are discussed as playing a critical role in the induction of polyneuropathies or neuropathic pain in different models ([ 16 , 17 , 18 , 19 , 20 ]. Several cation channels facilitate nociception, e.g., the transient receptor potential channels (TRP), a family of cation channels that are crucial transducers of nociceptive stimuli contributing to sensory input.…”
Section: Introductionmentioning
confidence: 99%
“…Phase 2 clinical trials conducted with BMS-986020 ( 48 ), a potent LPA1 receptor antagonist, demonstrated that LPA1 receptor antagonists are effective in treating idiopathic pulmonary fibrosis; however, the study was terminated due to hepatotoxicity . Compounds such as 49 and UCM-05194 ( 50 ) which are LPA1 agonists have also been identified . Interestingly, 50 showed remarkable efficacy in reducing neuropathic pain in the mouse spared nerve injury (SNI) model of neuropathic pain .…”
Section: Approaches To Develop Safer Ligands For New Pain Targetsmentioning
confidence: 99%
“…Compounds such as 49 and UCM-05194 ( 50 ) which are LPA1 agonists have also been identified . Interestingly, 50 showed remarkable efficacy in reducing neuropathic pain in the mouse spared nerve injury (SNI) model of neuropathic pain . Thus, both LPA1 antagonists which block the LPA1 receptor and LPA1 agonists which cause desensitization of the receptor can be pursued in the development of novel treatments for neuropathic pain.…”
Section: Approaches To Develop Safer Ligands For New Pain Targetsmentioning
confidence: 99%
“…LPA is a lysophospholipid that is a potent lipid-signaling molecule with many different actions in the CNS including neural development (Hecht et al, 1996 ), axonal retraction (Bräuer et al, 2003 ; Broggini et al, 2010 ), neuronal death (Kingsbury et al, 2003 ; Steiner et al, 2006 ; Ramesh et al, 2018 ; Zhang et al, 2020 ), and inflammation (Kwon et al, 2018 ; Plastira et al, 2020 ). Moreover, LPA signaling has been related to various neurological disorders including psychiatric diseases (Mirendil et al, 2015 ; Yamada et al, 2015 ; Schneider et al, 2018 ; Tabbai et al, 2019 ), Alzheimer’s disease (Hwang et al, 2012 ; Shi et al, 2013 ; Ramesh et al, 2018 ) spinal cord injury (Goldshmit et al, 2012 ; Santos-Nogueira et al, 2015 ; López-Serrano et al, 2019 ), and the appearance of neuropathic pain responses (Lin et al, 2012 ; Ueda et al, 2013 , 2018 ; González-Gil et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%